The effect of accrual earnings management, using Khotari Model Approach, on the performance of manufacturing companies listed in Indonesia Stock Exchange - Mochamad Handoko; Nurmala Ahmar (The Indonesian Accounting Review, 2015)
The purpose of this study is (1) to analyze the effect of accrual earnings management on the company performance measured with Return On Assets (ROA), (2) to analyze the effect of accrual earnings management on the company performance measured with Tobin’s Q. This study uses the data of manufacturing companies listed in Indonesia Stock Exchange. The sampling technique used is purposive sampling method. The researcher uses Khotari Model to calculate discretionary accruals as the proxy of earn-ing management, while the company performance in this study is proxied by the indi-cators of Return on Assets (ROA) and Tobin’s Q. The analysis technique used is descriptive analysis and simple linear regression. The results of this study prove that accrual earnings management affects ROA and Tobin’s Q. This study also proves that there is a decline in market value when the earnings management is performed.